Emergence of a clinical isolate of E. coil ST297 co-carrying blaNDM-13 and mcr-1.1 in China - Xiaofan Zhang; Lei Peng; Yefang Ke; Dongdong Zhao; Guoqing Yu; Ying Zhou; Xi Li; Xingbei Weng (Elsevier, 2023)
Background: The coexistence of carbapenem resistance genes and mcr-1.1 in Enterobacterales has been an urgent and persistent threat to global public health. In this study, we isolated a clinical NB4833, an Escherichia coli isolate that co-carries mcr-1.1 and blaNDM-13. Objectives: This study aimed to isolate a clinical NB4833, an Escherichia coli isolate that co-carries mcr-1.1 and blaNDM-13 and investigated the phenotypic and genotypic characteristics of plasmids harbored by E. coli isolate NB4833. Methods: Antimicrobial susceptibility testing and conjugation assay were performed on E. coli isolate NB4833. Stability of the plasmid and growth rate determination were used to characterize the plasmids harboring mcr-1.1 and blaNDM-13. In addition, the genetic characteristics of the plasmids were analyzed based on whole-genome sequencing of the strain and comparative genetic analysis with related plasmids. Results: Whole-genome sequencing showed that the isolate carried multiple resistance genes and possessed phenotypes indicative of all antibiotic resistance except tigecycline. And the mcr-1.1- and blaNDM-13-harbouring plasmids showed relatively high similarity to the related plasmids. The pNB4833-NDM-13 plasmid was capable of trans conjugation with an efficiency of 1.04 × 10−2 in a filter mating experiment and the transconjugant J53/ pNB4833-NDM-13 was able to be stably inherited after 10 days of passage. Conclusions: To our knowledge, this is the first report of the coexistence of the IncI2 plasmid carrying mcr-1.1 and a blaNDM-13-carrying integrated IncFIB/IncFII plasmid in an ST297 clinical E. coli isolate. In addition, we investigated a novel plasmid carrying blaNDM-13. Our study expands the diversity of plasmids carrying blaNDM-13, which exhibits epidemic importance in bacterial resistance. Therefore, there are important measures that should be taken to prevent the spread of these plasmids.